Active or Inert? An Experimental Comparison of Creative Ideation across Incubation Periods. (15th November 2019) - Frith, Emily; Ponce, Pamela; Loprinzi, Paul D.
Abstract: The primary objective of this study was to contribute to the growing research discipline investigating the effects of physical exercise on divergent thinking creativity performance. Thirty‐two students participated in this two‐visit, within‐subject intervention. Individuals consented to participate in two randomized, and counterbalanced, experimental conditions, consisting of 15 min of active treadmill walking and an inert, seated control incubation period. Creativity was assessed at baseline and post‐exercise (and control) via the Instances Creativity Task (ICT). Creativity scores for changes in fluency ( F (1, 31) = 2.90, p  = .10) were not statistically significant across the experimental conditions. Originality scores were higher at baseline and follow‐up when compared to the exercise condition ( F (1, 31) = 6.82, p  = .01). However, there was no statistically significant condition × time interaction effect ( F (1, 31) = 1.78, p  = .19). Further analyses demonstrated that there was no statistically significant difference between the experimental conditions on recall score ( F (1, 31) = 1.04, p  = .32). All models indicated statistically significant main effects for time: fluency ( F (1, 31) = 131.17, p  < .001); originality ( F (1, 31) = 36.54, p  < .001); and recall ( F (1, 31) = 51.75, p  < .001). These findings suggest that both active and inert creative incubation periods may similarly enhance subsequent divergent thinking performance.